DISPARITIES OF PUNISHMENT AGAINST PEOPLE OF THE CRIME OF ABORTION (Analysis Decision Number 01/ Pid.B /2013/ PN.Plp and Decision Number 242/ Pid.Sus /2015/ PN.Kpg ) - Muhammad Rafandi Harahap; Andry Syafrizal Tanjung; Mhd Azhali Siregar (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Various form problems that occur in handling case follow criminal abortion that is exists disparity criminal in matter his punishment . Problem the the source is judge's decision . Power judiciary as something free and independent state power in one side bring huge impact​ positive to effort enforcement law in Indonesia. Writing This use study law descriptive , which is in study This writer use type study juridical normative use method Research data collection References . Study This For know How accountability criminal to perpetrator follow criminal abortion , implementation law to perpetrator follow criminal abortion , in analysis decision number : 01/ Pid.B /2013/ PN.Plp and decision number : 242/ Pid.Sus /2015/ PN.Kpg . Based on results research and discussion then get it picture , that accountability criminal perpetrator do follow criminal abortion arranged in Articles 299, 346-349 of the Criminal Code and regulated in Articles 75-77 and Article 194 of the Law Number 36 of 2009 Concerning Health . Application law to the perpetrator did it follow criminal abortion analysis decision Number 01/ Pid.B /2013/ PN.Plp and Number 242/ Pid.Sus /2015/ PN.Kpg , that before drop criminal to the defendant , the judge has base considered considerations​ from charges and facts at trial . Analysis decision Palopo District Court Already in accordance with the elements charged prosecutor prosecutor general which the judge decides with based charges and facts at trial , vs backwards with the Kupang District Court The Panel of Judges did not consider indictment prosecutor prosecutor second general​ that is elements chapter more dominant proven inside​ facts the judge Because perpetrator abortion No is from power medical or power health so that give rise to oddity rule law in the position process applied law​ to perpetrator follow criminal different abortions​ to two decision perpetrator follow criminal abortion .